Thesis Selection for Music Professional Degree in China in Recent Years - Ding, Luona (Journal of Theory and Practice of Contemporary Education, 2023)
When students write their thesis, topic selection plays an important role. The academic value of the selected topic is closely related to the smooth writing and completion of the paper. So, for students majoring in music, we will discuss the problems encountered during the topic selection of their thesis and provide scientific guidance for the selected students. Therefore, this study has certain significance.